Heme oxigenase-1 na infecção de células trofoblásticas vilosas e extravilosas humanas por Toxoplasma gondii - Almeida, Marcos Paulo Oliveira (2018)
Heme oxygenase-1 (HO-1) is an enzyme responsible for heme catabolism, with the iron (Fe2+) release in addition to carbon monoxide (CO) and bilirubin formation, that present a cytoprotective role, wherein the control of their expression and activity, mainly requires, differential phosphorylation of mitogen-activated protein kinases (MAPKs). HO-1 is also involved in the immune response to infective microorganisms, such as Toxoplasma gondii, an obligate intracellular parasite protozoan that causes toxoplasmosis, a severe disease in immunocompromised individuals and pregnant women. The human placenta, in turn, is an essential structure to maternal-fetal communication, whose villous and extravillous trophoblast cells are embryonic/fetal cell populations, which contribute to generation of an immune tolerance in the maternal organism, important for pregnancy maintenance. Due to the contribution of HO-1 on functions of these cells, which are susceptible to T. gondii infection, the present study evaluated the influence of this enzyme on the infection of human villous trophoblast cells (BeWo line) and extravillous (HTR-8/SVneo line) by the parasite. BeWo and HTR-8/SVneo cells were infected or not, with T. gondii, treated or not with hemin, a porphyrin and inductor of HO-1, being analyzed to the cellular viability and T. gondii proliferation rates. Also the HO-1 expresssion and activity associated with the phosphorylation/activation of p38, JNK e ERK1/2 (MAPKs) and cytokines production (MIF, IL-6, IL-8, IL-10 and TNF) were analyzed. In both cells, the results showed that although treatment with hemin reduced slightly the cellular viability, T. gondii proliferation was increased with porphyrin stimulus. Under infection, BeWo cells presented lower expression and activity of the enzyme, which remained unchanged in HTR-8/SVneo cells. In this context, activation of p38-MAPK was associated with reduced HO-1 expression in BeWo cells, whereas in HTR-8/SVneo cells, phosphorylation of JNK was enhanced by treatment with hemin. In addition, infection, with or without induction of HO-1, was able to increase the production of MIF, IL-6 and IL-8 by BeWo or HTR-8/SVneo cells. Taken together, our data suggest that T. gondii infection decrease the HO-1 expression and activity, mainly, in BeWo trophoblast cells.